Active energy ray-curable antifogging composition and resin molding

JP2025030052APending Publication Date: 2025-03-07STANLEY ELECTRIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023135018
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-03-07

Smart Images

  • Figure 2025030052000001_ABST
    Figure 2025030052000001_ABST
Patent Text Reader

Abstract

To provide an active energy ray-curable antifogging composition and a resin molding which are excellent in antifogging properties and durability.SOLUTION: A solventless active energy ray-curable antifogging composition 10 contains a radically reactive material containing a hydrophilic group 11, a polyfunctional acrylate, and a compound represented by the following general formula (1) and has a viscosity of 10 to 60 mPa s. (In the general formula (1), each A independently represents a hydrogen atom or a methyl group; and n represents 0 or 1.)SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an active energy ray-curable anti-fogging composition and a resin molded article. [Background technology]

[0002] Transparent synthetic resins such as polycarbonate resin (PC) and polymethyl methacrylate resin (PMMA) are excellent in transparency, moldability, and mechanical properties, and are therefore used in many fields, such as lamp covers for automobiles and motorcycles, eyeglass lenses, optical sensor covers, and various liquid crystal panels. However, there is a problem that scratches or dirt on the surface of a molded product such as a synthetic resin can reduce light transmittance, causing poor visibility and malfunction of sensors, etc. In order to prevent such problems, a composition is applied to the surface of a molded product such as a synthetic resin to ensure transparency (scratch resistance, etc.).

[0003] For example, Patent Document 1 discloses a composition containing 3-methyl-1-methacryloyloxy-3-butene and a polyfunctional compound, in which the polyfunctional compound (B) is a polyvalent (meth)acrylic acid ester having two or more (meth)acryloyloxy groups in the molecule or a hydroxyl-containing polyvalent (meth)acrylic acid ester having two or more (meth)acryloyloxy groups in the molecule. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 7194176 Summary of the Invention [Problem to be solved by the invention]

[0005] However, on the surface of a molded product such as a synthetic resin cured from such a composition, when the surface temperature falls below the dew point temperature, moisture in the air condenses into fine droplets, causing fogging, which reduces light transmittance, leading to poor visibility and malfunction of sensors, etc.

[0006] The present invention has been made in view of the above-mentioned points, and an object of the present invention is to provide an active energy ray-curable anti-fogging composition and a resin molding which are excellent in anti-fogging properties and durability. [Means for solving the problem]

[0007] The active energy ray-curable anti-fogging composition of the present invention comprises: A solvent-free active energy ray-curable anti-fogging composition, The active energy ray-curable anti-fogging composition comprises a radical-reactive material having a hydrophilic group, a polyfunctional acrylate, and a compound represented by the following general formula (1), and has a viscosity of 10 to 60 mPa s: [ka] (In the general formula (1), each A independently represents a hydrogen atom or a methyl group, and n represents 0 or 1). [Brief description of the drawings]

[0008] [Figure 1] 1 is a conceptual diagram showing a resin molded article of the present invention. [Diagram 2] 1A to 1C are diagrams illustrating a manufacturing process of a resin molded article according to the present invention. [Diagram 3] 1 is a table summarizing the results of comparison between Examples and Comparative Examples of the active energy ray-curable anti-fogging composition of the present invention. [Figure 4] FIG. 1 is a conceptual diagram showing a conventional resin molded body. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] An embodiment of the present invention will be described below. The active energy ray-curable anti-fogging composition 10 of the present invention contains a radical reactive material, a multifunctional acrylate, a compound A, and an initiator, and has a viscosity of 10 to 60 mPa·s.

[0010] The active energy ray-curable anti-fogging composition 10 is a solvent-free type. Here, "solvent-free type" means that the active energy ray-curable anti-fogging composition 10 does not contain a non-reactive volatile organic solvent or substantially does not contain a non-reactive volatile organic solvent. "Substantially does not contain a non-reactive volatile organic solvent" means that when the active energy ray-curable anti-fogging composition 10 is subjected to gas chromatography analysis at 200°C, the total amount of components detected as having a structure not containing a vinyl group or an acryloyl group is less than 1 mass%.

[0011] Since the active energy ray-curable anti-fogging composition 10 is a solvent-free type, when the active energy ray-curable anti-fogging composition 10 is cured, most of it becomes a cured film as an active ingredient, so that the total amount of the active energy ray-curable anti-fogging composition 10 required for coating the surface of the substrate 20 can be reduced.

[0012] The radical reactive material contains a hydrophilic group. As shown in Fig. 1, when an active energy ray curable anti-fogging composition 10 is applied to the surface of a substrate 20 (e.g., polycarbonate resin), at least a part of the hydrophilic group 11 is disposed on the surface layer of the active energy ray curable anti-fogging composition 10. Then, by curing the active energy ray curable anti-fogging composition 10 by a radical reaction, a cured film having a hydrophilic group can be formed on the surface of the substrate 20.

[0013] Since the hydrophilic group is disposed on the surface of the active energy ray-curable anti-fogging composition 10, the surface of the active energy ray-curable anti-fogging composition 10 has a hydrophilic function. Therefore, the contact angle between the surface of the active energy ray-curable anti-fogging composition 10 and water can be reduced. Thus, moisture diffuses on the surface of the active energy ray-curable anti-fogging composition 10 to form a water film, and the anti-fogging properties of the substrate 20 can be ensured.

[0014] The radical reactive material is a radical reactive material made of a resin component such as a monomer or oligomer. By including the radical reactive material in the active energy ray curable anti-fogging composition 10, the viscosity of the active energy ray curable anti-fogging composition 10 can be reduced. Therefore, the active energy ray curable anti-fogging composition 10 can be used for coating without diluting with an organic solvent. Therefore, in the process of curing the active energy ray curable anti-fogging composition 10 on the surface of the substrate 20, a thermal drying process is not required, and power consumption during production can be reduced.

[0015] The content of the radical reactive material is preferably 70% by mass or more and less than 90% by mass with respect to the total amount of the active energy ray-curable anti-fogging composition 10. By making the content 70% by mass or more with respect to the total amount of the active energy ray-curable anti-fogging composition 10, the viscosity of the active energy ray-curable anti-fogging composition 10 can be adjusted to a suitable viscosity for spray coating without diluting it with an organic solvent. The suitable viscosity for spray coating is, for example, 10 to 50 mPa·s / 25°C.

[0016] Furthermore, if the content of the radical reactive material is less than 70% by mass, the surface of the cured film cannot have a sufficient hydrophilic function, and fogging of the substrate cannot be prevented. On the other hand, if the content of the radical reactive material is 90% by mass or more, sufficient adhesion to the hydrophobic substrate 20 cannot be ensured.

[0017] Examples of radical reactive materials that can be used include polyethylene glycol diacrylate, triethylene glycol diacrylate, pentaerythritol triacrylate, 2-hydroxy-3-acryloyloxypropyl acrylate, polytetramethylene glycol diacrylate, etc. These radical reactive materials may be used alone or in combination of two or more kinds.

[0018] The multifunctional acrylate is a hydrophobic material with high reactivity. By containing the multifunctional acrylate in the active energy ray curable anti-fogging composition, the curing speed of the active energy ray curable anti-fogging composition 10 can be increased. In addition, the highly reactive multifunctional acrylate cures, and the radical reactive material having a hydrophilic group cures later. Therefore, the multifunctional acrylate that is compatible with the hydrophobic substrate adheres to the substrate, and the hydrophilic material that cures later is likely to be arranged on the outermost surface. Therefore, a thin film of the hydrophilic material can be applied to the surface of the cured film, and the anti-fogging property can be further improved.

[0019] Since the polyfunctional acrylate is hydrophobic, it can improve the adhesion between the active energy ray curable anti-fogging composition 10 and the substrate 20 when applied to the hydrophobic substrate 20. Therefore, it is possible to suppress peeling of the cured film from the substrate 20. In addition, since the adhesion between the cured film and the substrate 20 is high, it is also possible to suppress the occurrence of cracks in a low temperature environment. Therefore, it is possible to form a cured film with excellent durability on the substrate 20.

[0020] The content of the polyfunctional monomer is preferably 1% by mass or more and less than 10% by mass with respect to the total amount of the active energy ray curable anti-fog composition 10. When the content of the polyfunctional monomer is less than 1% by mass, sufficient adhesion to the hydrophobic substrate cannot be ensured. On the other hand, when the content of the polyfunctional monomer is 10% by mass or more, the proportion of hydrophilic groups is relatively decreased, so that sufficient anti-fog properties cannot be imparted to the substrate. In addition, when the content of the polyfunctional monomer is 10% by mass or more, the viscosity of the active energy ray curable anti-fog composition increases, and the dischargeability during spray coating decreases, making spray coating difficult.

[0021] As the polyfunctional monomer, dipentaerythritol hexaacrylate, trimethylolpropane ethoxy triacrylate, dipentaerythritol hexaacrylate, etc. can be used.

[0022] Compound A is represented by the following general formula (1). [ka] (In the general formula (1), each A independently represents a hydrogen atom or a methyl group, and n represents 0 or 1).

[0023] For example, compound A is isoprenyl methacrylate (IPEMA) when A in general formula (1) is a methyl group and n is 1. Compound A is allyl methacrylate when one A in general formula (1) is a methyl group and the other A is a hydrogen atom and n is 1.

[0024] When the active energy ray curable anti-fogging composition is cured as a thin film, the curing of the active energy ray curable anti-fogging composition may be insufficient due to oxygen inhibition. However, the active energy ray curable anti-fogging composition 10 containing the compound A is prevented from being inhibited by oxygen curing. Therefore, the occurrence of water drip marks due to insufficient curing of the active energy ray curable anti-fogging composition can be prevented.

[0025] The content of compound A is preferably 0.1% by mass or more and less than 5.0% by mass with respect to the total amount of the active energy ray-curable anti-fogging composition 10. When the content of compound A is less than 0.1% by mass, the oxygen absorption effect is insufficient and the occurrence of water drip marks cannot be sufficiently suppressed. On the other hand, when the content of compound A is 5.0% by mass or more, the reactivity of the active energy ray-curable anti-fogging composition is deteriorated, and water drip marks may occur.

[0026] 4 is a diagram showing a resin molded body 60 obtained by curing an active energy ray curable composition 40 not containing compound A on a substrate 50. As shown in FIG. 4, when an active energy ray curable composition 40 not containing compound A is cured on the surface of a substrate 50, a part of the active energy ray curable composition 40 is insufficiently cured due to the influence of oxygen inhibition, and the radical reactive material having a hydrophilic group with poor reactivity remains uncured and bleeds out on the surface of the substrate 50, and further water droplets 41 are generated by moisture, steam, water droplets 70, etc. As the radical reactive material having a hydrophilic group is eluted, the surface of the cured product becomes a hydrophobic coating, which reduces the anti-fogging function and generates fogging.

[0027] The initiator is a radical generator that generates highly active radicals when irradiated with ultraviolet light. These radical species undergo decomposition and react with resin components such as monomers and / or oligomers. This reaction product further reacts with another resin component, causing a chain reaction to proceed. Then, the crosslinking reaction proceeds, increasing the molecular weight, curing the radical reactive material and the polyfunctional acrylate, and forming a cured film.

[0028] The content of the initiator is preferably 0.1% by mass or more and less than 5.0% by mass with respect to the total amount of the active energy ray-curable anti-fogging composition 10. If the content of the initiator is less than 0.1% by mass, the curing of the active energy ray-curable anti-fogging composition becomes insufficient, resulting in curing failure. On the other hand, if the content of the initiator is 5.0% by mass or more, the molecular weight does not increase, resulting in insufficient strength of the cured film.

[0029] Examples of the initiator include ketones such as benzophenone, benzoin methyl ether, benzoin propyl ether, diethoxyacetophenone, and 1-hydroxycyclohexyl phenyl ketone; azos such as 2,2'-azobisisobutylnitrile, azobis-2-methylbutyronitrile, and azobisdivaleronitrile; organic peroxides such as t-butylperoxyisobutyrate, t-butylperoxy-2-ethylhexanoate, t-amylperoxy-3,5,5-trimethylhexanoate, t-butylperoxyisopropylcarbonate, 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, di-t-butyl peroxide, and di-t-amyl peroxide; and acylphosphine compounds such as 2,6-dimethylbenzoyldiphenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. Among these, radical cleavage type initiators such as 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, etc. are preferred. These initiators may be used alone or in combination of two or more.

[0030] In addition to the initiator, the active energy ray-curable anti-fogging composition 10 may contain various additives such as an antibacterial agent, an antifungal agent, an antifoaming agent, an antioxidant, an antistatic agent, and a polymerization inhibitor.

[0031] Examples of antibacterial agents include captan, carbendazim, quinomethionate, chlorothalonil, clozolinate, cyprodinil, epoxiconazole, famoxadone, fenarimol, fenbuconazole, fenfuram, fenpiclonil, azoxystrobin, benalaxyl, benomyl, bitertanol, fluazinam, fludioxonil, fluorimide, fluquinconazole, flusulfamide, flutolanil, folpet, Hexachlorobenzene, hexaconazole, ipoconazole, iprodione, kresoxim methyl, manzeb, maneb, mepanipyrim, mepronil, metconazole, metiram, phthalide, procymidone, propineb, quintozene, tecnazene, thifluzamide, thiophenate methyl, thiram, tolclofos methyl, tolylfluanid, triadimefon, triadimenol, triazoxide, triforine, etc. can be used. Inorganic antibacterial agents can also be used, for example, silver, copper, zinc, tin, lead, gold, etc. Furthermore, synthetic antibacterial agents can also be used, for example, polyhexamethylene hyguanide, hydrochloride, benzethonium chloride, alkyl polyaminoethyl glycine, benzisothiazoline, etc.

[0032] As the mildewproofing agent, for example, sodium dehydroacetate, sodium benzoate, sodium pyridinethione-1-oxide, p-hydroxybenzoic acid ethyl ester, 1,2-benzisothiazolin-3-one and salts thereof can be used.

[0033] Examples of the defoaming agent that can be used include fatty acid salts, liquid fatty oil sulfates, higher alcohol sulfates, fatty alcohol phosphates, fatty acid amide sulfonates, sulfonates of dibasic fatty acid esters, alkylarylsulfonates, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, sorbitan alkyl esters, polyoxyethylene sorbitan alkyl esters, acrylic polymers, vinyl polymers, and organopolysiloxanes.

[0034] As the antioxidant, for example, a phenol-based antioxidant, a phosphorus-based antioxidant, a sulfur-based antioxidant, etc. can be used. As the phenol-based antioxidant, for example, 2,6-di-tert-butyl-p-cresol, stearyl β-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate, 1,3,5-trimethyl-2,4,6-tris(3',5'-di-tert-butyl-4-hydroxybenzyl)benzene, etc. can be used. As the phosphorus-based antioxidant, for example, tris(2,4-di-tert-butylphenyl)phosphite, diphenyl mono(2-ethylhexyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)-2-ethylhexylphosphite, distearyl pentaerythritol diphosphite, tri(mononylphenyl)phosphite, etc. can be used. As the sulfur-based antioxidant, for example, dilauryl-3,3'-thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), etc. can be used.

[0035] Examples of the antistatic agent that can be used include various cationic antistatic agents having cationic groups such as primary to tertiary amino groups, quaternary ammonium salts, and pyridinium salts; anionic antistatic agents having anionic groups such as sulfonate groups, sulfate groups, phosphate groups, and phosphonate groups; amphoteric antistatic agents such as amino acid-based and amino sulfate-based; nonionic antistatic agents such as amino alcohol-based, glycerin-based, and polyethylene glycol-based; and polymeric antistatic agents obtained by increasing the molecular weight of the above-mentioned antistatic agents.

[0036] A polymerization inhibitor may be added to prevent the double bond from reacting. Examples of the polymerization inhibitor include hydroquinone (HQ), hydroquinone monomethyl ether (MEHQ), 2,6-di-t-butyl-4-methylphenol (BHT), t-butylcatechol (TBC), and phenol or naphthol derivatives such as 4-methoxy-1-naphthol, phenothiazine derivatives, and nitrosamine salts.

[0037] A method for producing a resin molded body 30 in which an active energy ray curable anti-fogging composition 10 is cured on the surface of a substrate 20 will be described with reference to FIG. 2. First, the active energy ray curable anti-fogging composition 10 is loaded into a paint gun (S1). Then, the substrate 20 to be coated is fixed to a coating jig (S2). The active energy ray curable anti-fogging composition 10 is applied to the surface of the substrate 20 with a paint gun so as to have a uniform film thickness of less than 10 μm (S3). The active energy ray curable anti-fogging composition 10 is irradiated with ultraviolet rays (S4). The active energy ray curable anti-fogging composition 10 is cured on the surface of the substrate 20 to form a cured film (S5). As described above, a resin molded body 30 in which the active energy ray curable anti-fogging composition 10 is cured on the surface of the substrate 20 can be produced.

[0038] When applying the active energy ray-curable anti-fogging composition 10 to the surface of the substrate 20, the composition may be applied to a part of the surface of the substrate 20, or may be applied to the entire surface of the substrate 20. The method for applying the active energy ray-curable anti-fogging composition 10 is not limited to a coating gun, and an application method using an inkjet or a dispenser may also be used.

[0039] The substrate 20 may be made of a hydrophobic synthetic resin such as polymethyl methacrylate resin (PMMA) or a hydrophobic material such as glass, in addition to polycarbonate resin (PC).

[0040] The active energy ray-curable anti-fog composition 10 can be used as an anti-fog coating. The resin molded body 30 obtained by curing the active energy ray-curable anti-fog composition on the surface of a substrate can be used as an outer lens (translucent cover) of a vehicle lamp, a window glass, a lens of glasses, a cover for the surface of an optical sensor, and the like.

[0041] [Variation 1] The following describes Modification 1 of the active energy ray-curable anti-fogging composition of the present embodiment. Modification 1 of the active energy ray-curable anti-fogging composition is a solvent-free active energy ray-curable anti-fogging composition that contains a radical-reactive material, a multifunctional acrylate, compound A, an initiator, and a thiol material, and has a viscosity of 10 to 60 mPa s.

[0042] The thiol material is a compound containing a multifunctional thiol group. By including a thiol material in the active energy ray-curable anti-fogging composition 10, oxygen inhibition due to a thiol-ene reaction can be suppressed.

[0043] The reaction mechanism of the thiol-ene reaction is shown below. First, the initiator is cleaved or energy is transferred when ultraviolet light is irradiated (initiation reaction). Then, the initiator extracts an electron from the thiol material to generate a thiyl radical. The thiyl radical attacks the double bond of the monomer of the hydrophobic or hydrophilic material to form a hydrophobic or hydrophilic material having a thiol crosslink and a radical, which further abstracts hydrogen from the thiol material to generate a thiyl radical. The generated thiyl radical then attacks the double bond of another monomer of the hydrophobic or hydrophilic material (propagation reaction). In this way, the reaction proceeds in a chain reaction, and the active energy ray-curable anti-fogging composition 10 can be efficiently cured. [ka]

[0044] By including a thiol material in the active energy ray-curable anti-fogging composition 10, curing can be promoted by a dark reaction even in the air (oxygen atmosphere). The reaction mechanism in an oxygen atmosphere is shown below. First, oxygen reacts with a monomer to generate a peroxy radical. Then, the peroxy radical abstracts hydrogen from the thiol to generate a thiyl radical. The thiyl radical then undergoes the above-mentioned propagation reaction. Therefore, the active energy ray-curable anti-fogging composition can be cured even in an oxygen atmosphere. [ka]

[0045] By including a thiol material in the active energy ray-curable anti-fogging composition 10, a thioether crosslinked structure is formed, and the flexibility of the cured film can be increased. Therefore, the occurrence of cracks in a low-temperature environment can be suppressed, and durability can be further improved. Here, the flexibility of the cured film can be increased because the sulfur atom in the thioether crosslinked structure can move, such as rotate.

[0046] By including a thiol material in the active energy ray-curable anti-fogging composition 10, it is possible to suppress curing shrinkage. Curing shrinkage occurs when the double bonds of the radical reactive material are polymerized by radical polymerization, changing into a high molecular weight compound connected by single bonds, and the molecular bond distance is shortened. However, by including a thiol material, it is possible to suppress the shortening of the molecular bond distance by forming a thioether bridge with the double bonds of the radical reactive material. Therefore, curing shrinkage is suppressed, and the occurrence of defects such as cracks and warping of the cured film can be suppressed.

[0047] The content of the thiol material is preferably 1% by mass or more and less than 5% by mass with respect to the total amount of the active energy ray-curable anti-fogging composition 10. EXAMPLES

[0048] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0049] Example 1 In a 300 mL separable flask equipped with a stirring blade, 90 parts by mass of PEG200 diacrylate (product name: PEG200DA manufactured by Daicel Allnex Co., Ltd.) as a radical reactive material, 5 parts by mass of dipentaerythritol hexaacrylate (product name: Light Acrylate DPE-6A manufactured by Kyoeisha Chemical Co., Ltd.) as a multifunctional acrylate, and 2 parts by mass of isoprenyl methacrylate (product code: M3509 manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable anti-fogging composition of Example 1.

[0050] Example 2 In a 300 mL separable flask equipped with a stirring blade, 85 parts by mass of PEG200 diacrylate (product name: PEG200DA manufactured by Daicel Allnex Co., Ltd.) as a radical reactive material, 5 parts by mass of dipentaerythritol hexaacrylate (product name: Light Acrylate DPE-6A manufactured by Kyoeisha Chemical Co., Ltd.) as a multifunctional acrylate, 1 part by mass of isoprenyl methacrylate (product code: M3509 manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 5 parts by mass of pentaerythritol tetrakis (3-mercaptobutyrate) (product name: Karenz MT (R) PE1 manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 4 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184 manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable anti-fogging composition of Example 2.

[0051] Example 3 In a 300 mL separable flask equipped with a stirring blade, 90 parts by mass of PEG600 diacrylate (product name: EBECRYL 11, manufactured by Daicel Allnex Co., Ltd.) as a radical reactive material, 5 parts by mass of trimethylolpropane ethoxy triacrylate (product code: T0949, manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate, 1 part by mass of allyl methacrylate (product code: M0075, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 1 part by mass of pentaerythritol tetrakis(3-mercaptobutyrate) (product name: KarenzMT(R) PE1, manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 3 parts by mass of 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane (product name: Omnirad2959, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes, yielding 100 parts by mass of the active energy ray-curable anti-fogging composition of Example 3.

[0052] Example 4 In a 300 mL separable flask equipped with a stirring blade, 90 parts by mass of triethylene glycol diacrylate (product name: Light Acrylate 3EG-A, manufactured by Kyoeisha Chemical Co., Ltd.) as a radical reactive material, 3 parts by mass of trimethylolpropane ethoxy triacrylate (product code: T0949, manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate, 3 parts by mass of isoprenyl methacrylate (product code: M3509, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 1 part by mass of pentaerythritol tetrakis (3-mercaptobutyrate) (product name: Karenz MT (R) PE1, manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable anti-fogging composition of Example 4.

[0053] Example 5 In a 300 mL separable flask equipped with a stirring blade, 80 parts by mass of triethylene glycol diacrylate (product name: Light Acrylate 3EG-A, manufactured by Kyoeisha Chemical Co., Ltd.) as a radical reactive material, 15 parts by mass of trimethylolpropane ethoxy triacrylate (product code: T0949, manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate, 1 part by mass of isoprenyl methacrylate (product code: M3509, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 1 part by mass of trimethylolpropane tris(3-mercaptobutyrate) (product name: Karenz MT(R) TPMB, manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) were added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable anti-fogging composition of Example 5.

[0054] Example 6 Into a 300 mL separable flask equipped with a stirring blade, 10 parts by mass of pentaerythritol triacrylate (product name: Light Acrylate PE-3A manufactured by Kyoeisha Chemical Co., Ltd.) and 70 parts by mass of triethylene glycol diacrylate (product name: Light Acrylate 3EG-A manufactured by Kyoeisha Chemical Co., Ltd.) as radical reactive materials, 5 parts by mass of dipentaerythritol hexaacrylate (product name: Light Acrylate DPE-6A manufactured by Kyoeisha Chemical Co., Ltd.) as a multifunctional acrylate, 1 part by mass of isoprenyl methacrylate (product code: M3509 manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 1 part by mass of pentaerythritol tetrakis(3-mercaptobutyrate) (product name: Karenz MT(R) PE1 manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator, and the mixture was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray-curable anti-fogging composition of Example 6.

[0055] Example 7 In a 300 mL separable flask equipped with a stirring blade, 90 parts by mass of 2-hydroxy-3-acryloyloxypropyl acrylate (product name: Light Ester G-201P, manufactured by Kyoeisha Chemical Co., Ltd.) as a radical reactive material, 5 parts by mass of trimethylolpropane ethoxy triacrylate (product code: T0949, manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate, 1 part by mass of allyl methacrylate (product code: M0075, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 1 part by mass of 1,4-bis(3-mercaptobutyryloxy)butane (product name: Karenz MT(R) BD1, manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 3 parts by mass of 2-methyl-4'-(methylthio)-2-morpholinopropiophenone (product name: Omnirad907, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes, yielding 100 parts by mass of the active energy ray-curable anti-fogging composition of Example 7.

[0056] Example 8 Into a 300 mL separable flask equipped with a stirring blade, 60 parts by mass of 2-hydroxy-3-acryloyloxypropyl acrylate (product name: Light Ester G-201P, manufactured by Kyoeisha Chemical Co., Ltd.) and 30 parts by mass of polytetramethylene glycol diacrylate (product name: Light Acrylate PTMGA-250, manufactured by Kyoeisha Chemical Co., Ltd.) as radical reactive materials, 5 parts by mass of trimethylolpropane ethoxy triacrylate (product code: T0949, manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate, 1 part by mass of isoprenyl methacrylate (product code: M3509, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 2 parts by mass of 1,4-bis(3-mercaptobutyryloxy)butane (product name: Karenz MT(R) BD1, manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 2 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator, and the mixture was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray-curable anti-fogging composition of Example 8.

[0057] Example 9 In a 300 mL separable flask equipped with a stirring blade, 90 parts by mass of polytetramethylene glycol diacrylate (product name: Light Acrylate PTMGA-250, manufactured by Kyoeisha Chemical Co., Ltd.) as a radical reactive material, 5 parts by mass of trimethylolpropane ethoxy triacrylate (product code: T0949, manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate, 1 part by mass of isoprenyl methacrylate (product code: M3509, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 1 part by mass of pentaerythritol tetrakis (3-mercaptobutyrate) (product name: Karenz MT (R) PE1, manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 3 parts by mass of 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylpropane (product name: Omnirad2959, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes, yielding 100 parts by mass of the active energy ray-curable anti-fogging composition of Example 9.

[0058] Example 10 Into a 300 mL separable flask equipped with a stirring blade, 70 parts by mass of PEG600 diacrylate (product name: EBECRYL 11, manufactured by Daicel-Allnex Corporation) and 20 parts by mass of polytetramethylene glycol diacrylate (product name: Light Acrylate PTMGA-250, manufactured by Kyoeisha Chemical Co., Ltd.) as radical reactive materials, 5 parts by mass of trimethylolpropane ethoxy triacrylate (product code: T0949, manufactured by Tokyo Chemical Industry Co., Ltd.) as a multifunctional acrylate, 1 part by mass of isoprenyl methacrylate (product code: M3509, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A, and 1 part by mass of pentaerythritol tetrakis(3-mercaptobutyrate) (product name: KarenzMT(R) PE1, manufactured by Resonac Co., Ltd.) as a thiol material were added. Next, 3 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator, and the mixture was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray-curable anti-fogging composition of Example 10.

[0059] Comparative Example 1 In a 300 mL separable flask equipped with a stirring blade, 90 parts by mass of pentaerythritol (tri / tetra)acrylate (product name: Light Acrylate PE-3A, Light Acrylate PE-4A, manufactured by Kyoeisha Chemical Co., Ltd.) as a multifunctional acrylate and 5 parts by mass of isoprenyl methacrylate (product code: M3509, manufactured by Tokyo Chemical Industry Co., Ltd.) as compound A were added. Next, 5 parts by mass of 1-hydroxycyclohexyl phenyl ketone (product name: Omnirad184, manufactured by Sanyo Trading Co., Ltd.) was added as an initiator. This was stirred at room temperature for 30 minutes to obtain 100 parts by mass of the active energy ray curable composition of Comparative Example 1.

[0060] (Evaluation of dissolution) Each test piece, the surface of which was cured with the active energy ray-curable anti-fogging composition of Examples 1 to 10 or the active energy ray-curable composition of Comparative Example 1, was placed on a hot plate heated to 90°C, and 20 μL of pure water heated to 50°C was dropped onto the test piece. After that, the drop marks visible after the pure water was evaporated were visually checked to evaluate the elution property on a 5-level scale of A to E. The evaluation was performed as follows: A: when no trace of the eluted component was visible; B: when the trace of the eluted component was partially visible; C: when the trace of the eluted component was thin and spreading; D: when the trace of the eluted component was clearly visible; and E: when light was not transmitted due to the eluted component. FIG. 3 shows the evaluation results of the elution property of Examples 1 to 10 and Comparative Example 1.

[0061] (Evaluation of anti-fogging properties) Each test piece, the surface of which was cured with the active energy ray curable anti-fogging composition of Examples 1 to 10 or the active energy ray curable composition of Comparative Example 1, was immersed in 40°C warm water for 240 hours. Thereafter, the test piece was dried at room temperature, and breath was blown onto the test piece at room temperature. The surface area of ​​the test piece where fogging occurred was visually confirmed to evaluate the anti-fogging property on a 5-point scale of A to E. The evaluation was performed as follows: A: no fogging occurred on the test piece; B: about 10% of the surface area of ​​the test piece was fogging; C: about 50% of the surface area of ​​the test piece was fogging; D: about 80% of the surface area of ​​the test piece was fogging; and E: the entire surface area of ​​the test piece was fogging. FIG. 3 shows the evaluation results of the anti-fogging property of Examples 1 to 10 and Comparative Example 1.

[0062] (Condition evaluation in low temperature environment) Each test piece, in which the active energy ray-curable anti-fogging composition of Examples 1 to 10 or the active energy ray-curable composition of Comparative Example 1 was cured on the surface, was left in a freezer at -40°C for 240 hours. The test piece was then returned to room temperature, and the state of the cured film was visually checked to evaluate the state in a low-temperature environment on a 5-point scale of A to E. The evaluation was as follows: A: no cracks or fissures in the cured film; B: minor cracks in the cured film but no cracks; C: cracks in the cured film but no cracks; D: cracks and fissures in part of the cured film; and E: large cracks in the cured film. FIG. 3 shows the evaluation results of the state in a low-temperature environment for Examples 1 to 10 and Comparative Example 1.

[0063] (Evaluation of content of non-reactive volatile organic solvents) The active energy ray curable anti-fogging compositions of Examples 1 to 10 and the active energy ray curable composition of Comparative Example 1 were each subjected to gas chromatography analysis at 200°C to determine the total value of components detected in structures not containing vinyl groups or acryloyl groups. The evaluation was made as follows: A when the total value was less than 1 mass%, B when the total value was 1 mass% or more and less than 10 mass%, C when the total value was 10 mass% or more and less than 30 mass%, D when the total value was 30 mass% or more and less than 50 mass%, and E when the total value was 50 mass% or more. FIG. 3 shows the evaluation results of the content of non-reactive volatile organic solvents of Examples 1 to 10 and Comparative Example 1.

[0064] (Evaluation of ejection properties) The viscosity of the active energy ray-curable anti-fogging compositions of Examples 1 to 10 and the active energy ray-curable composition of Comparative Example 1 was measured and evaluated. The viscosity was measured using an E-type viscometer (product name: TVE-22L, manufactured by Toki Sangyo Co., Ltd.) in accordance with JIS K2283. The evaluation was made as follows: A when the viscosity was 3 mPa·s or more and less than 30 mPa·s, B when the viscosity was 30 mPa·s or more and less than 40 mPa·s, C when the viscosity was 40 mPa·s or more and less than 50 mPa·s, D when the viscosity was 50 mPa·s or more and less than 80 mPa·s, and E when the viscosity was 80 mPa·s or more. FIG. 3 shows the evaluation results of the dischargeability of Examples 1 to 10 and Comparative Example 1.

[0065] As is clear from Fig. 3, according to Examples 1 to 10, which are active energy ray curable anti-fog compositions containing a radical reactive material containing a hydrophilic group and compound A, it is clear that excellent dissolution properties and anti-fog properties can be ensured and the occurrence of cracks in the cured film in a low temperature environment can be suppressed. Therefore, a cured film having excellent anti-fog properties and durability can be formed. In this specification, "excellent dissolution properties" means that the components contained in the active energy ray curable anti-fog composition are unlikely to dissolve.

[0066] Moreover, it is clear that the content of non-reactive volatile organic solvents is reduced and excellent dischargeability can be ensured according to Examples 1 to 10, which are active energy ray-curable anti-fogging compositions containing a radically reactive material containing a hydrophilic group and compound A. Therefore, the ratio of the active ingredient that becomes the cured film is large, the total amount of materials can be reduced, and there is no need to dilute with an organic solvent when spray coating, which reduces power consumption during production.

[0067] From the results of Examples 2 to 10, it is clear that when a thiol material was contained, the cured film was not cracked or only slightly cracked when evaluated in a low-temperature environment, which indicates that the occurrence of cracks in a low-temperature environment could be further suppressed.

[0068] From the results of Examples 2 to 4, 6, and 9 to 10, it is clear that when pentaerythritol tetrakis(3-mercaptobutyrate) was contained as a thiol material, the cured film had no cracks in the condition evaluation under low temperature environment, and thus the occurrence of cracks under low temperature environment could be further suppressed.

[0069] The results of Examples 1, 2, and 6 show that when dipentaerythritol hexaacrylate was contained as a multifunctional acrylate, even if fogging occurred in the evaluation of anti-fogging property, it was only about 10% of the surface area of ​​the test piece, and in the evaluation of ejectability, the viscosity was less than 40 mPa s, so that it is clear that the anti-fogging property and ejectability are superior.

[0070] From the results of Examples 4 to 6, it is clear that when triethylene glycol diacrylate or pentaerythritol triacrylate is contained as the radical-reactive material, no traces of the eluted components are visible in the evaluation of elution, or even if any, they are only partial, which shows that the elution properties are superior.

[0071] From the results of Example 6, when pentaerythritol triacrylate and triethylene glycol diacrylate were contained as the radical-reactive material, no traces of eluted components were visible in the evaluation of elution, and no fogging occurred on the test pieces in the evaluation of anti-fogging property, so it is clear that the elution and anti-fogging properties were superior.

[0072] In contrast, in Comparative Example 1, which is an active energy ray-curable composition that does not contain a radical-reactive material having a hydrophilic group, the eluted components were clearly visible in the elution evaluation, and the eluted components prevented the transmission of LED light. In addition, in the anti-fogging evaluation, the entire surface of the test piece was fogged, and sufficient anti-fogging properties were not ensured. Furthermore, in the condition evaluation under a low-temperature environment, large cracks were found, indicating that low-temperature cracks are likely to occur, and the viscosity is 80 mPa·s or more, indicating that spray coating is not possible unless the composition is diluted with an organic solvent.

[0073] As described above, the active energy ray-curable anti-fogging composition and resin molded article of the present invention can ensure excellent anti-fogging properties and durability. [Explanation of symbols]

[0074] 10. Active energy ray-curable anti-fogging composition 11 Hydrophilic group 20 Base material 30 Resin molding 40 Active energy ray curable composition 41 Water Droplets 50 Base material 60 Resin molding 70 water drops

Claims

1. A solvent-free active energy ray-curable anti-fogging composition, The active energy ray-curable anti-fogging composition comprises a radical-reactive material having a hydrophilic group, a polyfunctional acrylate, and a compound represented by the following general formula (1), and has a viscosity of 10 to 60 mPa·s: 【Chemistry 1】 (In general formula (1), each A independently represents a hydrogen atom or a methyl group, and n represents 0 or 1).

2. The active energy ray-curable anti-fogging composition according to claim 1 , wherein the active energy ray-curable anti-fogging composition comprises a thiol material.

3. 3. The active energy ray-curable anti-fogging composition according to claim 2, wherein the thiol material is pentaerythritol tetrakis(3-mercaptobutyrate).

4. 2. The active energy ray-curable anti-fogging composition according to claim 1, wherein the radical reactive material comprises pentaerythritol triacrylate and triethylene glycol diacrylate.

5. A cured film obtained by curing the active energy ray-curable anti-fogging composition according to any one of claims 1 to 4; and a substrate having the cured film on at least a portion of its surface.

6. The resin molded article according to claim 5, wherein the substrate is hydrophobic.

7. 7. The resin molded article according to claim 6, wherein the substrate is a polymethyl methacrylate resin or a polycarbonate resin.

8. 6. The resin molding according to claim 5, which is an outer lens of a vehicle lamp.

Citation Information

Patent Citations

  • Composition with excellent curing properties

    JP7194176B2